Efektivitas Alat Tangkap Jaring Insang Hanyut pada Ikan Tongkol (Euthynnus sp.) diPerairan Seraya Timur, Bali - I Wayan Juliantara Putra; Elok Faiqoh; Widiastuti Widiastuti (Journal of Marine and Aquatic Sciences, 2021)
Tongkol fish (Euthynnus sp.) common types of fish resources found in the waters of Bali, especially Karangasem. Fishermen in Seraya Timur Village, Karangasem Regency, use drift gill nets to catch Tuna Fish. The use of drift gill nets is still very simple with the size of the mesh used that is also still diverse, but most use a mesh size of 2 and 2.5 inches. The use of drift gills by fishermen in the village of East Seraya is still very simple and the mesh nets used are also still diverse, but generally use mesh sizes of 2 and 2.5 inches. Therefore, it is necessary to know the level of effectiveness of each of the mesh sizes. The purpose of this study was to determine the amount of tuna fish catch using drift gill nets and the effectiveness of the two mesh sizes in the Seraya Timur waters. This study uses gill drift nets with 2 and 2.5 inch mesh sizes. The number of settings (decrease in net) and haulling (removal of the net) was carried out 22 times in March 2019. The results showed that the total number of catches with a 2 inch mesh size was relatively twice as high as the 2.5 inch mesh. It can be concluded that the net size of 2 inches has a smaller effectiveness compared to 2.5 inch mesh size.